Performance of hydroxycinnamic esters during white wine vinification - Penna, Neidi Garcia; Daudt, Carlos Eugenio; Henriques, João Antonio Pêgas (Pesquisa Agropecuaria Brasileira, 2001)
The objetive of this work was to quantify caftaric acid and cutaric acid in musts and wines during the vinification phases. White grape cultivars Chenin Blanc and Sauvignon Blanc (Vitis vinifera) cultivated in Santana do Livramento, RS, and Niágara (Vitis labrusca) cultivated in Santa Maria, RS, Brazil, were used in 1997, 1998 and 1999. Content of the compounds was determined through high performance liquid chromotography in grape crushing, during fermentation and when the wine was ready to be consumed. Generally, the caftaric acid concentrations were higher than the cutaric acid concentrations, in musts as much as in wine. The average quantity of caftaric acid in must, in the three cultivars, was 61.25 mg/L, while in the corresponding wine it was 32.10 mg/L, proving a decrease of this compound during fermentation. A similar performance was observed for cutaric acid (22.63 and 9.00 mg/L, respectively for must and wine). In samples collected six months after bottling, a decrease was also observed in these two compounds, but in a smaller proportion.